Using Simulation to Measure and Improve Pediatric Primary Care Offices Emergency Readiness. Issue 3 (June 2020) - Garrow, Amanda L.; Zaveri, Pavan; Yuknis, Matthew; Abulebda, Kamal; Auerbach, Marc; Thomas, Eileen M.
Abstract : Introduction: Emergencies in the pediatric primary care office are high-risk, low-frequency events that offices may be ill-prepared to manage. We developed an intervention to improve pediatric primary care office emergency preparedness involving a baseline measurement, a customized report out with action plans for improvement (based on baseline measures), and a plan to repeat measurement at 6 months. This article reports on the baseline measurement. Methods: This baseline measurement consisted of 2 components: preparedness checklists and in situ simulations. The preparedness checklists were completed in person to measure compliance with the American Academy of Pediatrics Policy Statement: preparation for emergencies in the offices of pediatricians and pediatric primary care providers, in the domains of equipment, supplies, medication, and guidelines. Two in situ simulations, a child in respiratory distress and a child with a seizure, were conducted with the offices' interprofessional teams; performance was scored using checklists. Results: Baseline measurements were conducted in 12 pediatric offices from October to December 2018. Wide variability was noted for compliance with the American Academy of Pediatrics recommendations (range = 47%–87%) and performance during in situ simulations (range = 43%–100%). Conclusions: Pediatric primary care office emergency preparedness was found to be variable. Simulation can be used to augment existing measures of emergency preparedness, such as checklists. By using simulation to measure office emergency preparedness, areas of knowledge deficit and latent safety threats were identified and are being addressed through ongoing collaboration.